لغزو الأسباني للمدن والموانئ الجزائرية وهران والمرسى الكبير أنموذجا 1505-1792م - الواعر, صبرينة (Université de M'sila, 2020)
ملخص: على الرغم من سقوط دولة المسلمين في الأندلس عام 1492م، غير أنّ اسبانيا لم تكتف بذلك وقررت ملاحقة المسلمين إلى الشمال الإفريقي؛ لكنها تفاجئت بقوة إسلامية جديدة قادمة من شرق حوض البحر الأبيض المتوسط، وهي القوة العثمانية، التي اكتسحت المتوسط واحتلت أجزاء عديدة منه، إلى أن وصلت بلاد المغرب مع مطلع القرن16م ، وهناك حدث الاحتكاك بين الأسبان والعثمانيين الذي تحوّل بعد وقت قصير إلى صراع على أشده عرف بالصراع الإسلامي المسيحي في البحر الأبيض المتوسط. مع ذلك تمكنت إسبانيا من وضع يدها على مينائي وهران والمرسى الكبير سنة 1505م خاصة لقربهما الجغرافي لمضيق جبل طارق. فيا ترى من هي دوافع الغزو الإسباني للسواحل الجزائرية؟ وهل للأمر علاقة بحركة الاسترداد المسيحي أم لأسباب أخرى؟ كلمات مفتاحية: إسبانيا.، العثمانيون.، بلاد.المغرب.، وهران.، المرسى.الكبير. Abstract: Despite the fall of the Muslim state in Andalusia in 1492 CE, Spain did not stop doing so and decided to pursue Muslims in northern Africa; but it was surprised by a new Islamic force coming from the eastern Mediterranean basin, the Ottomans power, which swept the Mediterranean and occupied many parts of it. Until the country of Maghreb the beginning of the 16 century, there was a friction between the Spaniards and the Ottomans that soon became a conflict of the most violent, known as the Christian Islamic conflict in the Mediterranean. However, Spain was able to hand over the ports of Oran and the Mers -El Kabir in 1505, especially for their geographical proximity to the Strait of Gibraltar. Via who are the motives behind the Spanish invasion of the Algerian coasts? Is the order linked to the Christian Recovery Movement (Reconquista) or for other reasons?
Keywords: Spain; The Ottomans; Maghreb Countries; Oran; Mers-El Kabir